2015
DOI: 10.1515/helmin-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenic Asian fish tapeworm, Bothriocephalus acheilognathi Yamaguti, 1934 (Cestoda) in the Red discus (Symphysodon discus)

Abstract: SummaryThe Asian fi sh tapeworm, Bothriocephalus acheilognathi Yamaguti, 1934, was detected for the fi rst time in breeding of discus fi sh Symphysodon discus (Perciformes, Cichlidae), a popular South American cichlid. In examined samples, the adult and juvenile cestodes of B. acheilognathi with mean intensity of infection 30 (range 19 -47) individuals per fi sh were found. The infected fi sh displayed acute behavioral symptoms. Mortality was signifi cant; it reached almost 80 % in youngest age categories. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(21 reference statements)
0
8
2
Order By: Relevance
“…The histopathological signs of S. acheilognathi in sh hosts are frequently extreme, with the parasite eventually killing its host (Brouder 1999). In the present study there was evidence of intestinal perforation and a large number (>600) of S. acheilognathi detected in each sh; far greater than previous studies, which have reported infection intensities of between 2 and 45 tapeworms (Scholz 1997;Brouder 1999;Košuthová et al 2015). In this study, the high intensity of tapeworms caused blockage and ischemia in parts of the intestines, resulting in intestinal perforations.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The histopathological signs of S. acheilognathi in sh hosts are frequently extreme, with the parasite eventually killing its host (Brouder 1999). In the present study there was evidence of intestinal perforation and a large number (>600) of S. acheilognathi detected in each sh; far greater than previous studies, which have reported infection intensities of between 2 and 45 tapeworms (Scholz 1997;Brouder 1999;Košuthová et al 2015). In this study, the high intensity of tapeworms caused blockage and ischemia in parts of the intestines, resulting in intestinal perforations.…”
Section: Discussioncontrasting
confidence: 61%
“…Lernaea cyprinacea was introduced to WA's native waterways as a co-invader with gold sh and now infects at least six native freshwater species (Hassan et al 2008). The original source of the S. acheilognathi in WA is unknown, but it appears that either goldish or koi carp are likely to be the source as these are the natural hosts for this particular parasite (Dove and Fletcher 2000;Košuthová et al 2015;Oros et al 2015;Salgado-Maldonado et al 2015;Kuchta et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bothriocephalus aceilognathi Yamaguti, 1934 are cestodes that affect mainly cyprinid fishes (family Cyprinidae), but can also be found parasitizing fishes from the families Poecilidae, Cichlidae, and Centrarchidae (Scholz, 1997). Kosuthová et al (2015) registered B. aceilognathi for the first time in the intestine of Symphysodon discus (Heckel, 1940) from Asia at a mean intensity of 30 worms per fish and 80% mortality. In C. auratus and Cyprinus carpio (Linnaeus, 1758), B. aceilognathi was observed at low prevalence, 7%, and 13%, respectively (Dove & Fletcher, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, monogeneans were mounted in Hoyer's medium to observe the sclerotized reproductive structures and identified according to Kritsky et al (1986); García-Vásquez et al (2007);Borisov (2013), and. Cestodes were stained with Gomori trichrome, clarified with beechwood creosote and posteriorly mounted between a slide and a coverslip, for the purpose of identification according to Kosuthová et al (2015). The nematodes were processed with regressive staining method and clarified with acetic acid for later analysis and measurements in the light microscope and identified according to Moravec (1987).…”
Section: Methodsmentioning
confidence: 99%